Characteristics of Peel-off Gel Mask Formulated from Jicama (Pachyhizus erosus) - Nguyen Ngoc Thanh Nguyen; Alfi Asben; Daimon Syukri (International Journal of Agricultural Sciences, 2022)
Food loss is a worldwide concern, especially the losses from the fresh tubers because of their quick rottenness during post-harvest without proper preservation. Meanwhile, the tuber is an excellent source of carbohydrates that can be used in a broad range of food and other industries. Therefore, creating added-value products from crops has been considered an intriguing idea for decades in order to reduce this matter and also can utilize raw materials from agriculture. This research aimed to determine and evaluate the effects of starch addition from Jicama on the characteristic of peel-off gel masks. Five different formulations were made with increased starch concentration at 1%, 2%, 3%, and 4%, and a control sample was formulated without adding starch. Organoleptic, spreadability, homogeneity, irritation, viscosity, pH, peeling time, and antibacterial and antioxidant activity were parameters in evaluating gel formulations. The best formula showed a homogenous consistency, there was no irritating reaction, and it had the highest sensory point from the panellist. The acidic degree and viscosity were 5.53 and 32867 cPs, respectively, which adhered to the Indonesian National Standard (SNI 2007) for facial skin products; the gel had good spreadability, and the peeling time was less than 30 minutes. Moreover, the gel presented an active antibacterial activity against Staphylococcus aureus; and antioxidant activity. According to the results, Jicama is recommended for application in making good quality peel-off gel mask products at 4% concentration.